Impact of GST on online purchase behaviour: A study of Bangalore consumers - Muneendra, Kayam; Ravikumar, Shruti; Asha, N (The International tax journal, 2026)
The implementation of the Goods and Services Tax (GST) in India has significantly transformed the indirect taxation system, influencing pricing transparency and consumer behaviour, particularly in the e-commerce sector. This study examines the impact of GST awareness, digital consumer engagement, and pricing perception on online purchase behaviour among consumers in Bangalore. The study adopts a descriptive and analytical research design, using primary data collected through a structured questionnaire from 434 respondents, of which 389 valid responses were analyzed. A 5-point Likert scale was employed, and data were analyzed using SPSS, incorporating descriptive statistics, Cronbach’s Alpha, correlation, regression, and ANOVA techniques. The results indicate strong reliability across constructs (α > 0.79) and significant positive relationships among variables (p < 0.01). Regression analysis reveals that the model explains 50% of the variance in purchase behaviour (R² = 0.50). Among the predictors, digital consumer engagement has the highest impact (β = 0.35), followed by pricing perception (β = 0.31) and GST awareness (β = 0.28). All hypotheses are supported, indicating that GST plays a significant role in shaping online consumer decisions. The study provides valuable insights for policymakers and e-commerce firms to enhance transparency and consumer trust.